2019
DOI: 10.3389/fpls.2019.00342
|View full text |Cite
|
Sign up to set email alerts
|

Tree Circumference Changes and Species-Specific Growth Recovery After Extreme Dry Events in a Montane Rainforest in Southern Ecuador

Abstract: Under drought conditions, even tropical rainforests might turn from carbon sinks to sources, and tree species composition might be altered by increased mortality. We monitored stem diameter variations of 40 tree individuals with stem diameters above 10 cm belonging to eleven different tree genera and three tree life forms with high-resolution dendrometers from July 2007 to November 2010 and additionally March 2015 to December 2017 in a tropical mountain rainforest in South Ecuador, a biodiversity hotspot with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…This coincides with other studies which have observed that Indigenous people from other areas use diverse seasonal calendars according to their cosmovision and ecological parameters based on where they inhabit (McKemey et al 2021 ). Regarding the VdN phenomenon, Raffelsbauer et al ( 2019 ) showed that it is characterized by a pronounced low-pressure system east of the Andes that weakens the dominant trade winds. This causes a reduction in cloudiness and the presence of higher outgoing longwave solar irradiance (OLR) under clear skies during the night, and the daily temperature range increases to approximately 25°C, from 2.4°C during the night to 27.1°C during the day (Bendix et al 2008 ; Rollenbeck and Bendix 2011a , 2011b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This coincides with other studies which have observed that Indigenous people from other areas use diverse seasonal calendars according to their cosmovision and ecological parameters based on where they inhabit (McKemey et al 2021 ). Regarding the VdN phenomenon, Raffelsbauer et al ( 2019 ) showed that it is characterized by a pronounced low-pressure system east of the Andes that weakens the dominant trade winds. This causes a reduction in cloudiness and the presence of higher outgoing longwave solar irradiance (OLR) under clear skies during the night, and the daily temperature range increases to approximately 25°C, from 2.4°C during the night to 27.1°C during the day (Bendix et al 2008 ; Rollenbeck and Bendix 2011a , 2011b ).…”
Section: Discussionmentioning
confidence: 99%
“…This causes a reduction in cloudiness and the presence of higher outgoing longwave solar irradiance (OLR) under clear skies during the night, and the daily temperature range increases to approximately 25°C, from 2.4°C during the night to 27.1°C during the day (Bendix et al 2008 ; Rollenbeck and Bendix 2011a , 2011b ). Taking advantage of the VdN phenomenon, and under paramo conditions (Raffelsbauer et al 2019 ), the Saraguro produce the low-severity burns (Fig. 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The course of daily stem circumference variation patterns (DSCCs) shows typical cycles, with stem shrinkage during daytime, when trees transpire more water than is replenished by the root system, and stem increment during nighttime due to stem water replenishment and irreversible growth caused by cambial activity (Deslauriers et al., 2007; Zweifel, 2016). Besides the leaf phenological status of the tree, its DSCCs depend on the short‐term weather conditions, showing characteristic diurnal patterns of stem increment and shrinkage, with variable amplitudes of DCC and radial growth during different seasons, but also during short‐term climatic episodes within one season (Raffelsbauer et al., 2019). The advantage of clustering DSCC patterns is that patterns occurring during different seasons of the year but representing similar plant physiological responses to the weather conditions are merged in one group of data, whereas in conventional time series analyses, tree responses are interpreted within the seasonal climate pattern (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Electric point or band dendrometers are valuable tools for monitoring continuous stem radial variations (SRV) and quantifying radial tree growth in high resolution [15,[27][28][29]. Dendrometer measurements allow the investigation of the influence of site conditions and meteorological factors on growth, as well as species-specific responses to changing climate conditions [30][31][32]. However, not all SRV are caused by radial growth, i.e., cambial division and cell expansion.…”
Section: Introductionmentioning
confidence: 99%